Political Uncertainty and Financial Market - Evidence from the US and European markets - Kuljukka, Laura (My University, 2019)
The purpose of this thesis is to measure the effects of political uncertainty on financial markets in the United States and Europe. Political uncertainty has achieved more attention during recent years on a global level. The reason behind the topic in this paper is the importance of understanding how the politically uncertain atmosphere affects the financial market. The other purpose of this paper is to compare differences of the effects of political uncertainty between different countries – are there differences between the United States and Europe or among European countries. Political uncertainty and risk have been researched in the United States to some extent, but less in Europe. Especially the presidential elections have been a popular way to measure political uncertainty. In this paper the economic policy uncertainty index is utilized as a proxy of political uncertainty. The economic policy uncertainty index has been researched in a few previous researches but there is still a gap to be filled under this topic. By utilizing the quantile regression model the changes in economic policy uncertainty index influence on stock indices are measured. The data is collected from 2009 to 2018. The results of this paper show that the changes in economic policy uncertainty index have the most significant effect in lower quantiles – in bear market conditions. This paper proves that the relationships between economic policy uncertainty index and countries’ stock indices are mainly negative in lower quantiles with the exception of France, where the relationship is positive. Economic policy uncertainty index has the biggest effect in Italy and Spain, while in the USA, Germany, the UK and France the effect is lower.
Keywords: Political Uncertainty; Political Risk; Stock Returns; Stock Index; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|